2D Phosphorene: 2D Phosphorene: Epitaxial Growth and Interface Engineering for Electronic Devices (Adv. Mater. 47/2018). Issue 47 (19th November 2018) - Zhang, Jia Lin; Han, Cheng; Hu, Zehua; Wang, Li; Liu, Lei; Wee, Andrew T. S.; Chen, Wei
Abstract : In article number1802207, Wei Chen and co‐workers highlight their recent progress in the interface engineering of 2D phosphorene for applications in both epitaxial growth and electronic devices. Their detailed investigations reveal the critical role of substrates for epitaxial growth of 2D phosphorene, demonstrate a highly efficient surface transfer doping method, and provide a comprehensive understanding of the oxidation mechanism of black phosphorus in air.